Resolution of Credit Agreement Disputes Due To Force Majeure From The Perspective of Syariah Banking - Addinur Addinur; Benny Djaja; Maman Sudirman (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the impact of recession on credit contracts in Islamic banking, especially in e-commerce activities. Murabahah-based credit contracts, which are used as financing products based on credit sales, involve the customer's obligation to pay installments according to the agreement. However, recessionary conditions create difficulties for customers in fulfilling their obligations, thus creating the potential for payment delays that can be detrimental to the bank. From an Islamic legal perspective, conditions beyond human control, such as recession, can be categorized as force majeure, which provides a legal basis for customers to delay payments. Legal resolution of this situation requires an approach that accommodates the principle of justice, where the imposition of fines for delayed payments is often viewed as a form of usury by some scholars, because it is considered an addition that is not in accordance with Islamic principles. This study aims to provide a comprehensive understanding of dispute resolution based on the concept of murabahah in Islamic banking, by considering the impact of recession on the sustainability of credit contracts, while offering solutions that are in line with Islamic legal principles and protection of the rights of customers and banks.